A step-by-step multiple stimuli-responsive metal-phenolic network prodrug nanoparticles for chemotherapy - Yi, Xiaoqing; Zeng, Weijia; Wang, Cui; Chen, Ying; Zheng, Liangyuan; Zhu, Xinlin; Ke, Yuqiu; He, Xiaoyan; Kuang, Ying; Huang, Qitong (Nano research, 2022)
Currently, chemotherapy is the main clinical therapy of tumors. Depressingly, most chemotherapeutic drugs such as doxorubicin and paclitaxel (PTX) have poor water solubility, leading to low bioavailability and serious side effects. Till now, although a variety of nanoparticulate drug delivery systems have been designed to ameliorate the above disadvantage of chemotherapy drugs, their application is still severely limited due to the complex preparation, poor stability, low drug loading, and premature drug release. Herein, a metal phenolic network-based drug delivery system with superior stability, satisfactory drug loading capacity, good biocompatibility, reduced undesired premature release, and excellent anti-tumor ability has been established for achieving step-by-step multiple stimuli-responsive drug delivery. Firstly, the redox-responsive dimeric paclitaxel (diPTX) prodrug was synthesized. Then diPTX@Fe&tannic acid (diPTX@Fe&TA) complex nanoparticles with satisfactory PTX loading capacity were obtained by deposition of Fe&TA network complex on the nanocore of diPTX rapidly with a simple method. The diPTX@Fe&TA nanoparticles have a hydrodynamic diameter of 152.6 ± 1.2 nm, long-term colloidal stability, and high PTX loading content of 24.7%. Besides, diPTX@Fe&TA could expose to the acidic lysosomal environment and the reduction cytoplasmic environment continuously, resulting in the sequential release of diPTX and PTX when it was phagocytosed by tumor cells. Meanwhile, PTX showed almost no release under physiological condition (pH 7.4), which effectively inhibited the undesirable premature release of PTX. More importantly, diPTX@Fe&TA could suppress the growth of tumor effectively in vivo , along with negligible toxicity for organs. This work developed a simple and novel approach for the construction of a stepwise multiple stimuli-responsive drug delivery system with superior stability and satisfactory drug loading capacity to inhibit tumor growth effectively.